2019
DOI: 10.1111/dme.13985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe diabetic kidney disease on the clinical outcome of autologous cell therapy in people with diabetes and critical limb ischaemia

Abstract: Aim To assess the impact of autologous cell therapy on critical limb ischaemia in people with diabetes and diabetic kidney disease. Methods A total of 59 people with diabetes (type 1 or type 2) and critical limb ischaemia, persisting after standard revascularization, were treated with cell therapy in our foot clinic over 7 years; this group comprised 17 people with and 42 without severe diabetic kidney disease. The control group had the same inclusion criteria, but was treated conservatively and comprised 21 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(45 reference statements)
3
2
0
Order By: Relevance
“…In contrast, the immunological profiles of patients with CLI did not significantly differ between baseline and the 6-month follow-up, suggesting that the delivery of allogeneic P-MSCs was completely safe. This finding is consistent with prior safety findings from comparable clinical studies [ 42 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the immunological profiles of patients with CLI did not significantly differ between baseline and the 6-month follow-up, suggesting that the delivery of allogeneic P-MSCs was completely safe. This finding is consistent with prior safety findings from comparable clinical studies [ 42 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…The immunological pro les of patients with CLI did not signi cantly differ between baseline and the 6-month follow-up, suggesting that the delivery of allogeneic P-MSCs was completely safe. This nding is consistent with prior safety ndings from comparable clinical studies (42)(43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study confirmed that intramuscular autologous transplantation of MSCs to no-option CLI patients is safe, with no adverse events or SAEs attributable to BM harvest, cell therapy or injection procedure. This result supports the preexisting safety data reported by previous similar clinical trials [7,9,11,[21][22][23]. In this study, two cell doses were examined (20 and 40 million MSCs), with three patients treated with the low-dose and one patient treated with the higher dose.…”
Section: Discussionsupporting
confidence: 89%